Students’ Perception of the Use of AFDAL as LMS in English Language Classroom at SMPIT Al Fityan School Gowa - Firdaus, Firawati; G, Hasriani; Sofyan, Ryan Rayhana (Journal of Excellence in English Language Education, 2024)
This research aims to determine students' perceptions of the use of AFDAL as an LMS in the English class of SMPIT Al Fityan School Gowa. Researchers apply qualitative methods to achieve research objectives. The data collected was in the form of questionnaires and interviews. The subjects of this research were class VIII students of SMPIT Al Fityan School Gowa for the 2022/2023 academic year. The questionnaire sample was 53 students and interviews were 6 students taken using the Purposive Sampling technique. The results of data analysis based on three TAM constructs, Perceived Ease of Use, Perceived Usefulness, and Attitude Toward Using, show that students' perceptions of using AFDAL as an LMS are in a good category. Therefore, it can be concluded that class VIII students at SMPIT Al Fityan School Gowa have a good perception of the use of AFDAL LMS in learning English.